Reversible cholinesterase inhibitors as pre-treatment for exposure to organophosphates: assessment using azinphos-methyl - Petroianu, Georg A; Nurulain, Syed M; Hasan, Mohamed Y; Kuča, Kamil; Lorke, Dietrich E (JAT. Journal of applied toxicology, 2015)
Pre-treatment with reversible acetylcholinesterase (AChE) inhibitors before organophosphorous compound (OPC) exposure can reduce OPC-induced mortality. However, pyridostigmine, the only substance employed for such prophylaxis, is merely efficacious against a limited number of OPCs. In search of more efficacious and broad-range alternatives, we have compared in vivo the ability of five reversible AChE inhibitors (pyridostigmine, physostigmine, ranitidine, tacrine and K-27) to reduce mortality induced by the OPC azinphos-methyl. Protection was quantified using Cox analysis by determining the relative risk (RR) of death in rats that were administered these AChE inhibitors in equitoxic dosage (25% of LD01) 30 min before azinphos-methyl exposure. Azinphos-methyl-induced mortality was significantly reduced by all five tested compounds as compared with the reference group that was only exposed to azinphos-methyl without prior pre-treatment (RR = 1). The most efficacious prophylactic agents were K-27 (RR = 0.15) and physostigmine (RR = 0.21), being significantly more efficacious than ranitidine (RR = 0.62) and pyridostigmine (RR = 0.37). Pre-treatment with tacrine (RR = 0.29) was significantly more efficacious than pre-treatment with ranitidine, but the difference between tacrine and pyridostigmine was not significant. Our results indicate that prophylactic administration of the oxime K-27 may be a promising alternative in cases of imminent OPC exposure. Copyright © 2014 John Wiley & Sons, Ltd.
Keywords: proporcionální rizikové modely; Proportional Hazards Models; Dose-Response Relationship, Drug; pyridinové sloučeniny; Rats; vztah mezi dávkou a účinkem léčiva; cholinesterasové inhibitory; ranitidin; takrin; Tacrine; Cholinesterase Inhibitors; mužské pohlaví; Rats, Wistar; Oximes; Ranitidine; Pyridostigmine Bromide; krysa rodu Rattus; azinfos-methyl; Pyridinium Compounds; Azinphosmethyl; zvířata; fysostigmin; Physostigmine; pyridostigmin-bromid; potkani Wistar; oximy; Male; Animals